Introductory Reflection: Peru's Forests from a Complex Perspective - Sabogal-Dunin-Borkowski, Ana (2023)
Essay on the issue of the situation of forests in Peru. It presents, in a concise manner, the contributions of the articles from the special dossier «Forests and Sustainable Development in Peru: An Interdisciplinary Perspective». It includes reflections on the actions and policies that the State has been carrying out; analysis of how businesses and the population use forests, some from a historical perspective and others with more contemporary approaches. The texts in the dossier are presented according to the classic division of Peruvian geography: coast, highlands, and jungle.